2015
DOI: 10.1097/moo.0000000000000176
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin in the management of facial paralysis

Abstract: BT continues to be a well tolerated and effective tool in the long-term management of facial paralysis, specifically in treating synkinesis, imbalance and hyperkinesis, as well as hyperlacrimation and pseudoptosis. Consistent measurement tools and adjunct neuromuscular retraining are crucial in the successful deployment of BT. Controversy exists as to whether BT should be used to manage facial paralysis during the acute phase, and whether BT application to the nonparalyzed face can improve long-term recovery i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 49 publications
0
32
0
3
Order By: Relevance
“…Facial synkinesis is a difficult disorder to treat, often requiring both a combined medical and surgical approach. Chemodenervation is successful in providing temporary relief and improved quality of life by taking advantage of clostridium botulinum's distinct neurotoxic effects . In a 1996 meta‐analysis, Dutton et.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Facial synkinesis is a difficult disorder to treat, often requiring both a combined medical and surgical approach. Chemodenervation is successful in providing temporary relief and improved quality of life by taking advantage of clostridium botulinum's distinct neurotoxic effects . In a 1996 meta‐analysis, Dutton et.…”
Section: Discussionmentioning
confidence: 99%
“…Facial synkinesis is the involuntary contraction of muscles in combination with voluntary movements that develop after facial denervation or nerve injury. The treatment of the disorder is predominantly physical therapy and chemodenervation, with select adjunct surgical procedures . There are several agents used for chemodenervation, although all contain the clostridium botulinum neurotoxin.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated the ability of botulinum toxin to treat synkinesis and hypertonicity in patients with NFFP. 9,10,29,30 Chemodenervation for NFFP is associated with improved clinician-graded assessment of facial palsy severity and patient-reported QOL scores. 31,32 Not only can botulinum toxin be used to improve hypertonicity and synkinesis, but it can also be administered to musculature on the healthy side to improve symmetry.…”
Section: Management Of Nffp Historical Treatmentsmentioning
confidence: 99%
“…17,100 Ultimately, facial reanimation outcomes may be optimized with multimodal approaches utilizing a combination of chemodenervation as well as static and dynamic procedures to address functional and aesthetic impairment. 101…”
Section: Surgical Management Of Facial Paralysismentioning
confidence: 99%